Activated cytotoxic T cells within zoonotic cutaneous leishmaniasis lesions. Issue 3 (17th April 2019) - Boussoffara, Thouraya; Boubaker, Mohamed Samir; Ben Ahmed, Melika; Mokni, Mourad; Feriani, Salma; Ben Salah, Afif; Louzir, Hechmi
Abstract: Introduction: Zoonotic cutaneous leishmaniasis (ZCL), due to infection by Leishmania (L). major, is characterized by polymorphic clinical manifestations which could be attributed to the host's immune response. In this study we investigated the involvement of cytotoxic cells on the outcome of the disease. Methods: Expression of granzyme B (GrB), granulysine (Grly), and interferon (IFN)‐γ was evaluated within ZCL lesion specimens using the technique of real‐time quantitative polymerase chain reaction (RT‐qPCR). Immunohistochemical staining was performed using anti‐CD3, CD4, CD8, CD56, GrB, and IFN‐γ antibodies to identify the phenotype of GrB and IFN‐γ‐producing cells. Results: GrB and Grly mRNA was detected within 75% and 80% of ZCL lesions, respectively. Statistical analysis demonstrated a significant correlation between levels of GrB and Grly. Interestingly, expression of these molecules correlates negatively with the lesion's age. The highest levels were measured in early lesions (E‐ZCL) (lesion age ≤1 month) comparing to late lesions (L‐ZCL) (lesion age >1 month). Otherwise, IFN‐γ mRNA was detected only within 56% and a positive correlation was found between levels of this cytokine and those of GrB. Immunohistochemical analysis showed that GrB is produced essentially by CD8 + T cells whereas IFN‐γ is produced by both CD4 + and CD8 + T cells. Conclusion: Together our results demonstrate the presence of cytotoxic cells producing GrB and Grly within leishmaniasis cutaneous lesions. Abstract : The aim of this study is to investigate the role of cytotoxic cells on the outcome of the Zoonotic cutaneous leishmaniasis (ZCL) due to infection by Leishmania major. We demonstrated the presence of cytotoxic T lymphocytes expressing high levels of granzyme B and granulysine within ZCL lesions comparing to healthy skin. Immunohistochemical analysis showed that GrB is produced essentially by CD8+T cells.